Greening U.S. legacy cities: urban agriculture as a strategy for reclaiming vacant land. Issue 8 (14th September 2017) - Carlet, Fanny; Schilling, Joseph; Heckert, Megan
ABSTRACT: Repurposing vacant land for food production is expanding as a response to urban blight, food insecurity, and food deserts. As municipalities integrate urban agriculture in their sustainability plans and zoning regulations, scholars are beginning to take a broader look at the benefits from this and other types of greening strategies. This article investigates current state of research and practice of urban agriculture as an emerging strategy for regenerating shrinking cities. It highlights key findings while offering observations on how public officials and practitioners can leverage this research to enhance urban agriculture as a treatment for vacant land.